BRCA Germline Mutations in Women With Uterine Serous Carcinoma-Still a Debate. Issue 9 (1st November 2010) - Lavie, Ofer; Ben-Arie, Alon; Segev, Yakir; Faro, Jonathan; Barak, Frida; Haya, Nir; Auslender, Ron; Gemer, Ofer
Abstract : Objective: To determine the incidence of BRCA1 and BRCA2 mutations in an enlarged series of uterine serous carcinoma (USC) patients and to determine whether patients with USC are associated with a personal or familial history of breast or ovarian carcinoma. Methods: A cohort of all consecutive patients with diagnosed USC was identified for 9 years. Family pedigrees were drawn as far back and laterally as possible. In all patients, genomic DNA was extracted from peripheral blood samples and analyzed for the 3 mutations common in Ashkenazi Jewish patients. All patients went through total abdominal hysterectomy, bilateral salpingo-oophorectomy, and omentectomy. Tubal, ovarian, and peritoneal carcinoma were ruled out clinically and pathologically in all patients. Results: Of 51 consecutive patients with USC in Ashkenazi Jews studied, we identified 13 patients (25.5%) who were previously found to have breast carcinoma, 17 patients (33.3%) who had a first-degree relative with breast or ovarian carcinoma, and 8 patients (15.7%) who were found to be carriers of 1 of the 3 BRCA germline mutations. Conclusions: This series of USC patients, the largest consecutive series to date, suggests a higher incidence of BRCA carriers among Ashkenazi Jews as compared with the general population. This high rate of BRCA germline mutations in USC patients coupled with a high rate of personal and familial cancer histories may suggest that USC is associated with the hereditary breast-ovarian syndrome. This potential association of USC to the BRCA-associated cancer spectrum may have implications for the clinical management and intervention of unaffected BRCA1-2 germline mutation carriers. However, at the current time, there are insufficient data to provide evidence-based guidelines regarding the optimal timing or specific intervention to prevent cancers in these high-risk women.